Community Health Centers for Resilient Communities in the post-COVID-19 era. (20th October 2021) - Buffoli, M; Gola, M; Mosca, EI; Ugolini, M; Lettieri, E; Capolongo, S
Abstract: Background: The synergy between territorial services and hospital organizations plays a crucial role for health promotion. Starting from the recent pandemic, the Community Health Centers (CHCs) could turn out particularly efficient in cases of high emergencies, avoiding the overflow of users in the hospital thanks to health home care management or low and medium-care facilities. The aim of the research is to identify evidence based experiences that supports the efficacy of design and management of CHCs, also during pandemics. Methods: The methodology is based on the analysis of several European case studies, selected by an extensive analysis of the main EU countries, through a comparative matrix with different criteria related to: a) general information; b) urban relationship with the healthcare territorial network; c) number of inhabitants and population basins; d) building typology, dimensions, flexibility and layout issues; e) healthcare staff involved, the number of workers and volumes of activities; f) sanitary and not sanitary functions before and during the COVID-19 pandemic, and transformations applied. Results: The analysis gives rise to several correlations due the localization of CHCs and the healthcare territorial network, dimensions and staff involved, sanitary and not sanitary functions -before and during the pandemic- and the flexibility of the CHCs, that permits to list experience based best practices for the design and management of resilient CHCs, as useful strategic lines for professionals in public health and healthcare design. The survey highlights the strategic role of CHCs for the healthcare territorial network with particular evidence during pandemics. Conclusions: The strategies aim to encourage the introduction of CHCs for the access to care for the population. The outcomes of the analysis are related to the research project Cities and Health Community Centers for Resilient Communities funded by PoliSocial Award 2020 of Politecnico di Milano. Key messages: definition of design and organizational strategies for Community Health Centers for Resilient Communities in the post-COVID-19 era. qualitative and quantitative data analysis of European Community Health Centers before and during the COVID-19 pandemic.